Interdisciplinary Applications of Glass Ionomer Cement in Dentistry, Dental Technology, Laboratory Sciences, and Dental Radiology - Alharbi, Ahad Hussain Shubikan; Jumanah Hassan Almubarak; Afnan Hussain Shubikan Alharbi; Norah Falah Alnawmasi; Thamer Abdullah Alothman; Reem Khaled Alamri; Mashal Mohammed Salem Alanazi; Fatimah Mohammed Nasir Alhazm; Hussain Khalid Alattiah; Hassan Hussain Alnasser; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Glass ionomer cement (GIC) is a widely used dental material known for its chemical adhesion to tooth structure, fluoride release, and biological compatibility, making it valuable across multiple dental disciplines. Since its development in the early 1970s, continuous modifications have expanded its clinical and interdisciplinary applications. Aim: This article aims to review the composition, properties, clinical indications, limitations, and interdisciplinary relevance of glass ionomer cement in dentistry, dental laboratories, and allied healthcare practice. Methods: A narrative review approach was employed, synthesizing existing scientific literature and clinical evidence related to the chemistry, setting mechanism, manipulation techniques, and clinical performance of conventional and modified glass ionomer cements. Results: Glass ionomer cement demonstrates reliable chemical bonding to enamel and dentin, sustained fluoride release with anticariogenic effects, and favorable biological responses. Advancements such as resin-modified, metal-reinforced, and high-viscosity formulations have improved handling characteristics, early strength, and moisture tolerance. However, limitations remain, including lower fracture resistance, reduced abrasion resistance, and esthetic constraints in high-stress or highly visible areas. Conclusion: Glass ionomer cement remains an essential restorative and preventive material when appropriately selected according to clinical demands. Its dentin-like properties, fluoride-mediated protection, and compatibility with interdisciplinary care continue to support its significant role in modern dental practice.